1995
DOI: 10.1148/radiology.196.2.7617860
|View full text |Cite
|
Sign up to set email alerts
|

Normal prostate gland: examination with color Doppler US.

Abstract: Transrectal color Doppler US can depict the vascular anatomy of the prostate gland. Knowledge of the normal vascular appearance of the gland should aid in the differentiation of normal from abnormal findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 0 publications
1
48
0
1
Order By: Relevance
“…Neumaier et al [14]have described CDUS findings of normal prostate well and correlated them with the normal vascular anatomy of the prostate. They described two parenchymal groups of arteries, urethral and capsular.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neumaier et al [14]have described CDUS findings of normal prostate well and correlated them with the normal vascular anatomy of the prostate. They described two parenchymal groups of arteries, urethral and capsular.…”
Section: Discussionmentioning
confidence: 99%
“…They described two parenchymal groups of arteries, urethral and capsular. The color flow signals in the lesions described in their article are mostly supplied by the capsular group of arteries [14]. In studies with CDUS, objective grading of the amount of flow signal is difficult and is different from paper to paper.…”
Section: Discussionmentioning
confidence: 99%
“…The urethral arteries, conversely, course parallel to the prostatic urethra after they enfold into the prostate at the bladder neck. 3 In this study, it was found that the mean value and geometric mean were higher for mean PI, mean RI, PSV and S/D in the malignant group than in the benign group, but none of the parameters were found statistically significant between the benign and the malignant groups. Huang and Hsieh 4 also showed that high-grade prostate cancer tends to have higher RI.…”
Section: 2mentioning
confidence: 52%
“…The prostatic vasculatures at bilateral NVB sites were analyzed in the largest transverse section of the prostate (Fig. 1) in accordance with reports by Leventis and colleagues 14 and Neumaier and colleagues 15 The arteries at the NVB sites were examined at the point just before they entered the prostate, rather than the intraprostatic branches penetrating into the gland. Once the pulsatile waveforms of a given Doppler spectrum became stable for the consecutive five repeats, the peak-systolic velocity (PSV), enddiastolic velocity (EDV), and the resistive index (RI) of each site were measured and recorded.…”
Section: Methodsmentioning
confidence: 96%